Imaging of Gastrointestinal Stromal Tumours with Modern Ultrasound Techniques − A Pictorial Essay - Dietrich, C. F.; Jenssen, C.; Hocke, M.; Cui, X.-W.; Woenckhaus, M.; Ignee, A. (Zeitschrift für Gastroenterologie, 2012)
Gastrointestinal stromal tumours (GIST) are rare tumours of the gastrointestinal tract. Dealing with these tumours requires a profound knowledge of the nature of the lesions and their malignant potentials. Modern ultrasound techniques provide the necessary tools to give the clinician the information he needs to diagnose and treat the patient. This article reviews the actual pathophysiological knowledge of GIST and provides a broad spectrum of ultrasound findings to introduce the reader into modern ultrasound investigation methods of subepithelial tumours. It covers the transcutaneous as well as the endoscopic ultrasound approach. Different conditions of GIST like the low risk or high risk form as well as the metastatic form will be discussed in diagnosis and treatment with plenty of examples. Special attention is paid to contrast-enhanced ultrasound techniques and elastography from the transcutaneous as well as the endoscopic route. Other diagnostic methods like CT, MRI and PET CT are additionally reviewed and their role in clinical practice is compared with that of ultrasound. The aim of the article is to introduce the reader into the new ultrasound techniques and special diagnostic behaviour of GIST and outline clinical pathways to deal correctly with different stages of the disease.
Keywords: leiomyoma; subepithelial tumours; guidelines